Ki-67 protein predicts survival in oral squamous carcinoma cells: an immunohistochemical study - Verena Karla Monteiro LOPES; Adriana Souza de JESUS; Lucas Lacerda de SOUZA; Ligia Akiko Ninokata MIYAHARA; Douglas Magno GUIMARÃES; Helder Antônio Rebelo PONTES; Flavia Sirotheau Correa PONTES; Pedro Luiz de CARVALHO (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study was to identify the expression of Ki-67 and MCM3 in oral squamous cell carcinoma (OSCC) as well as to address the correlation with patient survival and clinical features. Samples were collected from 51 patients with OSCC who presented for follow-up. Immunohistochemical expression of Ki-67 and MCM3 in all groups was performed. The scoring system was previous published by Tsurutani in 2005. We used Kappa index to evaluate observers agreement degree. The associations between protein expression and clinical variables were examined for statistical significance using the chi-squared test. The overall survival rates were estimated by the Kaplan-Meier method and the relationship between protein expression and survival was compared using the log-rank test (p < 0.05). The overall survival time for a patient with positive immunostaining for Ki-67 is shorter than for a patient with negative immunostaining, (log-rank test, p = 0.00882). Patients with tumor size T3 and T4 showed a statistically significant relationship with Ki-67 immunoexpression (log-rank test, p = 0.0174). The relationship between Ki-67 expression and the relation between age, gender, smoking, tumor site, lymph node metastasis and disease stage was not significant. The examiners agreement degree by Kappa presented p value < 0.05. There was not a significant correlation when we evaluated MCM3 expression regarding clinical characteristics and survival rate. From these results, the present study suggests that positive Ki-67 expression found in OSCC patients may contribute to predict the survival in OSCC samples, as well as the relation between the protein and the tumor size.